SciencePro Project: Towards Excellence in Bilingual Teaching - Natalia Barranco Izquierdo; Francisco Javier Sanz Trigueros; María Teresa Calderón Quindós; Ana Isabel Alario Trigueros (Universidad de Navarra, 2016)
This paper provides an account of the progress of SciencePro, an innovative, interdisciplinary and interinstitutional education project, whose ultimate aim is to improve student teachers' knowledge, abilities and attitudes for teaching Natural Sciences in a foreign language. The team is working on the development of good practices at university level: enhancing profi ciency of cross-curricular competences, including scientific contents, knowledge and foreign language skills oriented to scientific discourse, with a view to developing a more appropriate teaching approach. The Practicum period is needed in order to test out the improvement of these specific professional competences, which should be more suitable to modern bilingual school contexts.